Programming methodology for programmable automatas from Petri Nets - Alvarez Salazar, Johny Antonio (2019)
In this work is proposed a methodology for the programming of programmable automatas with TIA Portal from Petri Nets. In order to do it, an industrial application that requires to mix paints is selected, then a simulated process  that involves three tanks with their corresponding valves that activate for each one of them during an amount of time according to the color required in the preparation, three push buttons will select the color of the painting that you want to produce. Initially the Petri net is considered and then using of matrices the states equation is displayed for the trigger of all the transitions until returning to the initial state. The methodology establishes that after it the outputs must be associated to the different states and the transitions are associated to inputs. The Petri network is then translated into the programming language taking care to activate the next state and to deactivate the previous state according to the transition that occurs. Finally, the outputs are activated according to the states in which they were placed. When executing the simulation in the PLC, it was possible to verify the proper behavior of the sequence according to what was planned, thus demonstrating the effectiveness of the presented methodology.